2020
DOI: 10.1371/journal.pone.0232881
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pathway improves medical practice in total knee arthroplasty

Abstract: Clinical pathways in total knee arthroplasty (TKA) consist of general guidelines, including several topics as early rehabilitation and antibiotic systematization, which are used to improve patient's management, decrease complication rates and enhance clinical outcomes. The primary purpose of this study was to assess whether the use of a clinical pathway for TKA can contribute to reduce LOS and healthcare costs in a private hospital, without an increase in the hospital readmission rate. We also aimed to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
3
15
0
2
Order By: Relevance
“…18 19 Therefore, it is suggested that some factors may have contributed to the lower rates of dissatisfaction in our population compared with the literature, such as the socioeconomic profile of patients and, mainly, the implementation of a managed protocol for all TKAs performed at the institution after 2013, which standardized the patient care process and led to improvements in medical practice. 20 Similar to the satisfaction rate reported in the present study, there was also no significant difference in clinical scores of pain, function, and quality of life among patients younger or older than 65 years old, thus suggesting that TKA can be an effective treatment even in younger patients. It is interesting to note that although some studies have reported higher rates of dissatisfaction among younger patients, age may not be a predictive factor for dissatisfaction in itself.…”
Section: Discussionsupporting
confidence: 88%
“…18 19 Therefore, it is suggested that some factors may have contributed to the lower rates of dissatisfaction in our population compared with the literature, such as the socioeconomic profile of patients and, mainly, the implementation of a managed protocol for all TKAs performed at the institution after 2013, which standardized the patient care process and led to improvements in medical practice. 20 Similar to the satisfaction rate reported in the present study, there was also no significant difference in clinical scores of pain, function, and quality of life among patients younger or older than 65 years old, thus suggesting that TKA can be an effective treatment even in younger patients. It is interesting to note that although some studies have reported higher rates of dissatisfaction among younger patients, age may not be a predictive factor for dissatisfaction in itself.…”
Section: Discussionsupporting
confidence: 88%
“…Foni et al. described that the implementation of CP in TKA was related to a reduction in the length of hospital stay from 6.3 to 4.9 days, and a reduction in cost compared with the control group [ 121 ]. Schwarzkopf et al.…”
Section: Implementation Of Eras: From Protocol To Practicementioning
confidence: 99%
“…Furthermore, it increased the rate of administration of prophylactic antibiotics, within 60 min, prior to the incision from 87.4 to 99.2%. Moreover, the rate of discontinuation of prophylactic antibiotics within 48 h increased from 51.6 to 84.7% 18 . CP implementation was associated with less antibiotic use in a retrospective study on patients undergoing endoscopic retrograde cholangiopancreatography for common bile duct stones 19 .…”
Section: Discussionmentioning
confidence: 99%